(untitled) (European Journal of Pure and Applied Mathematics, 2025)
A set S of vertices of a graph G is a disjunctive dominating set if for every vV(G)S, v is adjacent to a vertex in S or S contains two vertices each of distance two from v. A disjunctive dominating set S is a connected disjunctive dominating set if S is connected. In this paper, we study the concept of connected disjunctive dominating set.